Acid Row - Walters, Minette (London Macmillan, 2001)
Acid Row - a no-man's land where angry, alienated youth controls the streets. Sophie Morrison, a young doctor is trapped at the centre of a terrifying seige, with a known paedophile. Young Amy is missing and the mob want retribution, no matter what the cost.
Keywords: England -- Child molesters -- Women physicians